Building and codifying the Hikmat Al-Madhkhori and Abbas Saadoun test to measure the accuracy of scoring after changing the direction by rolling for futsal players - Al-Madhkhori, Hikmat; Saadoun, Abbas (sports creativity, 2025)
The researchers addressed the importance of developing and standardizing a test to measure scoring accuracy after changing direction while rolling, as skill tests are one of the scientific methods that enable experts in the field of sports to determine the extent of the impact and relationship of skill aspects on the desired results, including changing direction while rolling and scoring accuracy for futsal players. This is a specialized addition to the subject of sports testing and measurement. The test sample consisted of players from the Maysan Governorate Futsal Team in the advanced category. The test was conducted in the indoor hall at the Technical Institute in Maysan from December 28, 2016, to January 31, 2017. The researchers used a descriptive survey method, with the research community consisting of 72 players from the Maysan Governorate first division futsal team and clubs. The research sample (Maysan province team) was selected deliberately and consisted of eight right-footed players from the Maysan team, which had a total of 12 players. The research also included another sample to construct and standardize the test designed by the researchers, consisting of first division clubs (Maysan, Maysan Oil, Qalaat Saleh, Kamit, and Al-Sukkar), numbering 60 players, and a preliminary sample of five players. The researchers constructed and standardized a test to measure the accuracy of scoring after changing direction by rolling for futsal players, and then standardized it by following the steps and procedures for constructing and standardizing measures and processing their data using the statistical package (SPSS). The researchers then reached the most important conclusions in constructing and standardizing a test to measure scoring accuracy after changing direction by rolling for advanced futsal players in Maysan, where it was found that futsal players (research sample individuals) have good accuracy in scoring with both feet, even though the research sample individuals were all right-footed players with a relative preference for the right side. The researchers recommend using this test to develop training programs for futsal players by improving their accuracy in scoring with both feet, given the significant role this plays in determining the outcome of matches, as well as conducting similar studies on futsal players in Iraq.